2002
DOI: 10.1007/s00223-001-1011-4
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Dentin Noncollagenous Matrix Proteins to Biological Mineral Crystals: An Atomic Force Microscopy Study

Abstract: Noncollagenous matrix proteins (NCPs) of dental hard tissues (dentin, cementum) are involved, both temporally and spatially, in the mineralization of their collagen matrices. Two of the NCPs thought to initiate mineral nucleation and control crystal growth in dentin, are dentin phosphoproteins (DPP) and dentin sialoprotein (DSP). Control of crystal growth would depend on the binding capacity of these two molecules, which may be related to the charge domains on the crystals and/or the phosphorylation of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 7 publications
2
36
0
1
Order By: Relevance
“…matrix-specific precipitation of calcium phosphate on its own but relies on several different noncollagenous proteins that control nucleation and initial progression of mineralization. 31,32,45,107 In contrast, enamel mineralization takes place within a noncollagenous protein matrix that is secreted by ameloblasts of epithelial origin. This enamel matrix consists of specialized proteins that regulate the structural development and mineralization of enamel.…”
Section: Discussionmentioning
confidence: 99%
“…matrix-specific precipitation of calcium phosphate on its own but relies on several different noncollagenous proteins that control nucleation and initial progression of mineralization. 31,32,45,107 In contrast, enamel mineralization takes place within a noncollagenous protein matrix that is secreted by ameloblasts of epithelial origin. This enamel matrix consists of specialized proteins that regulate the structural development and mineralization of enamel.…”
Section: Discussionmentioning
confidence: 99%
“…Dentin remineralisation has been shown to be influenced by the presence of phosphoproteins, since they have the ability to bind Ca [Lee et al, 1977;Zanetti et al, 1981]. Therefore, they may act as template for remineralisation when immobilised or tightly bound in the collagen matrix [Lussi et al, 1988;Hunter et al, 1996;Wallwork et al, 2002], or inhibit remineralisation when present in relatively higher concentrations and free in solution [Clarkson et al, 1991[Clarkson et al, , 1998]. Since demineralisation by organic acids, such as the citric acid used in this study, has not shown the ability to remove loosely bound phosphoproteins [Clarkson et al, 1998], it can be suggested that remineralisation can happen even in the presence of these proteins, when at levels of P i as high as in solution E. However, this has yet to be further verified.…”
Section: Discussionmentioning
confidence: 99%
“…The dsppnull mice have decreased mineral contents in both their dentin [109] and their long bones (unpublished data). The mild decrease in bone mineralization is a surprising finding as there are very low levels of DSP in bone and almost undetectable levels of DPP although the dspp gene is expressed by osteoblasts [110].…”
Section: Phosphoproteins (Siblings and Other Molecules)mentioning
confidence: 99%